Fire-resistant composite materials.
Although the benefits of using lightweight polymer composites are well known, their wider adoption has been hindered by uncertainty over their performance when subjected to extreme heat. Recently, EU-funded scientists have developed new materials that are either fire-resistant or provide protection with a minimum weight penalty.